2022
DOI: 10.1063/5.0076566
|View full text |Cite
|
Sign up to set email alerts
|

The L∞-deformations of associative Rota–Baxter algebras and homotopy Rota–Baxter operators

Abstract: A relative Rota–Baxter algebra is a triple ( A, M, T) consisting of an algebra A, an A-bimodule M, and a relative Rota–Baxter operator T. Using Voronov’s derived bracket and a recent work of Lazarev, Sheng, and Tang, we construct an L∞[1]-algebra whose Maurer–Cartan elements are precisely relative Rota–Baxter algebras. By a standard twisting, we define a new L∞[1]-algebra that controls Maurer–Cartan deformations of a relative Rota–Baxter algebra ( A, M, T). We introduce the cohomology of a relative Rota–Baxter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…As a biproduct of the above two cochain complexes, we construct a new complex defining the cohomology of the modified Rota-Baxter algebra (A, R) with coefficients in the bimodule (M, S). We compare our cohomology of modified Rota-Baxter algebras with the cohomology of Rota-Baxter algebras recently introduced in [13,33]. More precisely, we show that the cohomology of a Rota-Baxter algebra (A, P ) is isomorphic to the cohomology of the modified Rota-Baxter algebra (A, R = λ id + 2P ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a biproduct of the above two cochain complexes, we construct a new complex defining the cohomology of the modified Rota-Baxter algebra (A, R) with coefficients in the bimodule (M, S). We compare our cohomology of modified Rota-Baxter algebras with the cohomology of Rota-Baxter algebras recently introduced in [13,33]. More precisely, we show that the cohomology of a Rota-Baxter algebra (A, P ) is isomorphic to the cohomology of the modified Rota-Baxter algebra (A, R = λ id + 2P ).…”
Section: Introductionmentioning
confidence: 91%
“…This cohomology is obtained as a biproduct of the Hochschild cohomology of the underlying associative algebra A and the Hochschild cohomology of the induced associative algebra A R . We also compare our cohomology of a modified Rota-Baxter algebra with the cohomology of a Rota-Baxter algebra defined in [13,33].…”
Section: Cohomology Of Modified Rota-baxter Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…They further determined the L ∞ -algebra that controls deformations of a relative Rota-Baxter Lie algebra and introduced the notion of a homotopy relative Rota-Baxter Lie algebra of weight zero. Das and Misha [10] developed the corresponding weight zero cohomology theory for relative Rota-Baxter associative algebras and Das also introduced cohomology theory for relative Rota-Baxter associative algebras and relative Rota-Baxter Lie algebras of arbitrary weight [8,9]. Wang and Zhou [24,25] defined cohomology theory for relative Rota-Baxter associative algebras of arbitrary weights, determined the underlying L ∞algebra and also showed that the dg operad of homotopy Rota-Baxter associative algebras is the minimal model of that of Rota-Baxter associative algebras.…”
Section: Introductionmentioning
confidence: 99%
“…Algebraic structures are better understood by their extension theory and cohomology theory. Recently, such theories for Rota-Baxter algebras and dendriform algebras are studied in [10][11][12][13]22,24,31]. However, in the above-mentioned references, only the abelian extension theories are considered.…”
Section: Introductionmentioning
confidence: 99%